Editorial - Martha Cleveland-Innes (The Canadian Network for Innovation in Education (CNIE), 2024)
Welcome to Volume 50, Issue 1, of The Canadian Journal of Learning and Technology (CJLT). CJLT is a decades-old peer-reviewed journal that invites English or French submissions on the research and practice of education, technology, and learning. This bilingual journal is free-of-charge to anyone with access to the Internet, is multi-indexed, and presented in accessible formats. There are no article submission/publication fees or access charges.